Study of the academic composition in the vertical tripartite façades of the Masonic lodges in Nuevo León, 1905-1961 - Garza Martínez, Antonio (2022)
In the few buildings of masonic lodges in the state of Nuevo León, a composition with a common denominator of tripartition can be seen, which is apparently of academic inspiration. This paper will seek to identify the architectural elements that distinguish the façades of these Masonic lodges. An analysis will be made of the tripartite façades of these Masonic lodges, observing in their composition variations of both style and architectural language that are typical of the historical moment of their construction, as well as combining architectural decoration with the symbols of the fraternity.